Surgical Management for Giant liver Hemangiomas Greater Than 20 cm in Size - Jiang, Hui (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2011)
BACKGROUND/AIMS: The aim of this study was to investigate the primary management experience for giant liver hemangiomas greater than 20 cm in size. METHODS: Records of patients referred for evaluation of radiologically and/or histopathologically proven giant liver hemangiomas between January 2007 and March 2010 were retrospectively analyzed. The reasons for referral, results of imaging studies, preoperative and surgical treatments, and outcome were reviewed. RESULTS: A retrospective analysis was performed for 14 patients diagnosed with a giant hemangioma on the basis of an imaging study and/or a histopathological examination. All cases were diagnosed as giant liver hemangioma with at least one lesion greater than 20 cm in size. Abdominal discomfort was the main presenting complaint for the referral in 9 patients (64.2%). Abdominal ultrasound established the diagnosis in 12 patients (85.7%). Twelve patients underwent liver resection, 2 of whom underwent staged resection. Enucleation was performed in 2 patients. Selective transcatheter arterial embolization was implemented in 9 patients. Postoperative morbidity occurred in 3 patients (21.4%). No complications related to the hemangiomas occurred during follow up. CONCLUSIONS: Liver resection is indicated for giant liver hemangiomas with abdominal discomfort, especially for lesions greater than 20 cm in size. Staged operations are performed for patients with multiple lesions. Preoperative selective transcatheter arterial embolization alleviates progressive abdominal pain.